MODEL MANAJEMEN KOPERASI DALAM KEPEMIMPINAN WANITA PADA USAHA KOPERASI DI KABUPATEN JEMBER - Sunarsih, M. (Jurnal Sosial Ekonomi Pertanian, 2007)
Cooperation is helpfull to assist continuity of life socialize since coperation represent compatible for weak economics society, Over work improve be happened adding the level improvement live and the prosperity which have dreamed. Research target are (1.) To study management model from organizational at cooperation managed by woman in Jember regency (2.) To identify phenomenon that happened and activity of the cooperation managed by woman ( 3.) To know capital growth of cooperation that managed by woman and ( 4.) To know monetary growth of cooperation managed by woman in Jember regency. This research using “Comparative study” that comparing model of the cooperation managed woman and cooperation managed by men. The sample collected by Simple Random Sampling by five cooperations that are Sekar Kartini and Gladiol (managed by women) also KPRI Agrosejahtera, Kop Kar Aroma and KUD Rama managed by men. The analysis used at this research is descriptive analysis, tabulation statistic analysis, also ratio analysis of likuiditas, ratio of profitability, ratio of sovabilitas and operational ratio. The result shows that : ( 1)The membership growth of Kopwan Sekar Kartini and Gladiol are good enough, ( 2) Coordination among top management , board of examiner and co-op member is quite intensive that characterized by the attending in meeting (3)The capital growth is relatively good where Kopwan Sekar Kartini higher than Kopwan Gladiol.(4)Business activity efficient enough, especially at saving and loan activity (USP) to use group systems by system guarantee together method (5) Monetary growth at Kopwan Sekar Kartini And Gladiol tend to health posed at by ratio of Likuiditas, ratio of profitability and ratio of salvabilitas. Key words : Management model , cooperation managed by women